Examining the relationship between bright and dark personality traits in two management samples. (15th April 2019) - Wiens, Thomas K.; Walker, Lawrence J.
Abstract: There is considerable interest in finding ways to screen for dark personality traits (maladaptive interpersonal and personality tendencies) in personnel selection assessments given their pernicious effects on job performance and leadership behavior. This has proved challenging because of socially desirable response biases and ethical restrictions regulating the use of psychiatric measures. Recent advances in the understanding of the dimensional nature of personality suggest that measures of bright personality can be used to predict dark personality traits. The current research extends this research to the California Psychological Inventory (CPI) and employs multiple regression analyses to examine the bright–dark trait relationships in two samples of managers who underwent employment testing. Study 1 found that CPI scales significantly predicted each of the self-reported Hogan Development Survey dark traits. Study 2 extended this research to supervisor ratings and found that CPI scales significantly predicted 6 out of 11 dark traits as rated by supervisors. These studies further our understanding of the relationship between bright and dark personality traits and provide support for another method to screen for, and address the lack of observer assessments of, dark personality traits in workplace contexts. Highlights: Study 1: managers' bright traits predict their self-reported dark traits. Study 2: managers' bright traits predict supervisor ratings of their dark traits. California Psychological Inventory predicts Hogan Development Survey traits. Both studies occur in a high-stakes management-level hiring context.